Efektivitas Kegiatan Relawan Pajak RENJANI Dalam Mendorong Kesadaran Pajak Wajib Pajak Orang Pribadi di KPP Pratama Jakarta Kebon Jeruk Satu - Rahmahdina, Indira Dristi; Sahara, Ana Farida; Putra, Yananto Mihadi (Pelita : Jurnal Penelitian, Terapan dan Aplikatif, 2025)
The Tax Volunteer Program for the Country (Renjani) is an initiative of the Directorate General of Taxes (DGT) that aims to increase public tax awareness and compliance, especially individual taxpayers and MSMEs, through collaboration with universities and Tax Centers by empowering students as volunteers. The program is implemented through volunteers training, placement at Tax Offices (KPP) and Tax Centers, tax education, and MSME assistance in fulfilling tax obligations, with implementation locations including KPP Pratama Jakarta Kebon Jeruk Satu. The evaluation shows that Renjani is effective in increasing that reporting of Annual Tax Return (SPT) and strengthening public trust in DGT, thus demonstrating the importance of synergy between DGT and universities in encouraging voluntary tax compliance and supporting the optimization of state revenue for national development, which is relevant to be applied at KPP Pratama Kebon Jeruk Satu to encourage broader tax awareness of individual taxpayers.